2016
DOI: 10.1016/j.stem.2016.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Hematopoietic Stem Cells: Lessons from Development

Abstract: Summary Cell engineering has brought us tantalizingly close to the goal of deriving patient-specific hematopoietic stem cells (HSCs). While directed differentiation and transcription factor-mediated conversion strategies have generated progenitor cells with multilineage potential, to date, therapy-grade engineered HSCs remain elusive due to insufficient long-term self-renewal and inadequate differentiated progeny functionality. A cross-species approach involving zebrafish and mammalian systems offers complemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
86
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 120 publications
(193 reference statements)
2
86
0
2
Order By: Relevance
“…Zebrafish model. The zebrafish is an established model for studying hematopoiesis and development (25,26). At 26 hours post fertilization (hpf), expression data indicated ubiquitous staining for the zebrafish homolog srp54 (bottom image, Supplemental Figure 7A).…”
mentioning
confidence: 99%
“…Zebrafish model. The zebrafish is an established model for studying hematopoiesis and development (25,26). At 26 hours post fertilization (hpf), expression data indicated ubiquitous staining for the zebrafish homolog srp54 (bottom image, Supplemental Figure 7A).…”
mentioning
confidence: 99%
“…With an improving knowledge of stem cell niches and microenvironments [118,119] and technological advances, numerous factors have been identiied that regulate HSPC proliferation and diferentiation and some may potentially also control HSC self-renewal. Here, we will restrict our discussion to UCB expansion ex vivo and, as appropriate, discuss clinical applications, while other approaches to generate and assay (in xenograft in vivo models, e.g., in zebraish) patient-speciic HSPCs derived from ES or iPS cells have recently been reviewed and will not be discussed further [118].…”
Section: Further Cytokine and Small Molecule Addition To Expand Umentioning
confidence: 99%
“…Here, we will restrict our discussion to UCB expansion ex vivo and, as appropriate, discuss clinical applications, while other approaches to generate and assay (in xenograft in vivo models, e.g., in zebraish) patient-speciic HSPCs derived from ES or iPS cells have recently been reviewed and will not be discussed further [118].…”
Section: Further Cytokine and Small Molecule Addition To Expand Umentioning
confidence: 99%
“…Each stage is characterized by distinct transcriptional programs and expression of unique surface markers in addition to a subset of generic HSC markers (2). The early stages of HSC development provide important insights about the molecular programs that govern HSC origin and expansion (2,3). Most studies of HSC ontogeny are established in mouse models and the lack of common HSC markers between mice and human makes it difficult to isolate human HSCs with optimal purity (4).…”
mentioning
confidence: 99%
“…However, earlier studies in human cells suggest that EPCR is not associated with HSC activity in adult human BM (11). Recently, it was shown that UM171, a 3 Pyrimidoindole compound known to expand human long-term HSCs, upregulated EPCR expression in human UCB HSCs and that the EPCR positive fraction contained the engraftable HSCs (12,13). Gene expression profiling studies have further shown that EPCR is preferentially expressed in HSCs compared to multipotent progenitors (MPP) from both human UCB and FL (7,14).…”
mentioning
confidence: 99%